2022
DOI: 10.1016/j.chembiol.2021.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Probing the binding of interleukin-23 to individual receptor components and the IL-23 heteromeric receptor complex in living cells using NanoBRET

Abstract: Highlights d NanoBRET assays were created to monitor the interaction of IL-23 with its receptor d The affinities of IL-23 for IL23R, IL12Rb1 and heteromer complexes were measured d Receptor monomers were found to associate in complexes in the absence of IL-23 d IL-23 binding induced a rearrangement of the N-terminal domains of the receptor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 54 publications
(77 reference statements)
6
31
1
Order By: Relevance
“…In this study we validate the use of a previously reported TAMRA labelled version of IL-23 (IL23-TMR 24 ) for use in the characterisation of reported receptor antagonists at both IL23R and IL12Rβ1 and design and characterise a novel fluorescent cyclic peptide probe (P630-TMR) specific to the IL23R receptor subunit only. We then use P630-TMR to measure IL23R specific inhibitors, demonstrating how the probes can be used together to classify IL-23 receptor antagonists.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…In this study we validate the use of a previously reported TAMRA labelled version of IL-23 (IL23-TMR 24 ) for use in the characterisation of reported receptor antagonists at both IL23R and IL12Rβ1 and design and characterise a novel fluorescent cyclic peptide probe (P630-TMR) specific to the IL23R receptor subunit only. We then use P630-TMR to measure IL23R specific inhibitors, demonstrating how the probes can be used together to classify IL-23 receptor antagonists.…”
Section: Introductionsupporting
confidence: 57%
“…A possible explanation for the observed modulation in BRET efficiency with IL12Rβ1 is a modification of the position of the IL23R conjugated NanoLuc-tag caused by the association of the subunits in an inactive complex. The further reduction in BRET efficiency observed when the NanoLuc tag is placed on the N-terminus of IL12Rβ1 is most likely due to the increased distance between the N-terminus of IL12Rβ1 and the P630-TMR binding epitope, however the successful measurement of a BRET signal is consistent with the receptor subunits forming a complex in the absence of IL-23, as has been previously suggested 24,36 .…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations